Limit 2-Cycles for a Discrete-Time Bang-Bang Control Model - Chengmin Hou; Sui Sun Cheng (Discrete Dynamics in Nature and Society)
A discrete-time periodic model with bang-bang feedback control is investigated. It is shown that each solution tends to one of four different types of limit 2-cycles. Furthermore, the accompanying initial regions for each type of solutions can be determined. When a threshold parameter is introduced in the bang-bang function, our results form a complete bifurcation analysis of our control model. Hence, our model can be used in the design of a control system where the state variable fluctuates between two state values with decaying perturbation.